2009
DOI: 10.1002/ird.529
|View full text |Cite
|
Sign up to set email alerts
|

Local transformation of a state‐initiated institutional innovation: The example of water users' associations in an irrigation scheme in Morocco

Abstract: The international debate on participatory management and irrigation management transfer has mainly focused on ex-ante/ex-post evaluations that rely on quantitative performance indicators to measure the failure or success of management transfer and the functioning of water users' associations (WUAs). This article focuses on the appropriation by farmers of state-initiated WUAs illustrated by the case of the Moyen Sebou irrigation scheme in Morocco. This scheme, which was designed for agency-managed water distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
7

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 6 publications
0
8
0
7
Order By: Relevance
“…Thirdly, based on the revealed weaknesses and strengths, recommendations are made to improve functioning of the institutions and their outcomes. In most studies concerning the functioning of irrigation management performance, simple indicators are used (Lam, 2001;Malano et al, 2004;Yildirim & Cakmak, 2004;Kadiri et al, 2009). Such indicators, however, do not reveal the reasons for good or bad performance.…”
Section: Introductionmentioning
confidence: 98%
“…Thirdly, based on the revealed weaknesses and strengths, recommendations are made to improve functioning of the institutions and their outcomes. In most studies concerning the functioning of irrigation management performance, simple indicators are used (Lam, 2001;Malano et al, 2004;Yildirim & Cakmak, 2004;Kadiri et al, 2009). Such indicators, however, do not reveal the reasons for good or bad performance.…”
Section: Introductionmentioning
confidence: 98%
“…Dans le sens de Röling et Maarleveld (1999), la construction a influencé les concepts scientifiques et la conception des activités de recherche, notamment l'analyse de l'action collective mise en oeuvre par les agriculteurs , que celle-ci ait pour cadre des organisations professionnelles formelles (Kadiri et al, 2009) ou des arrangements informels (Boudjellal et al, 2011). L'expérience du réseau Raccord a aussi contribué à la mise en débat des savoirs locaux concernant l'action collective, en interaction avec l'action, et par la suite à leur généralisation.…”
Section: Discussion Et Conclusion Influencer Les Concepts Et Les Modèunclassified
“…Son expé-rience dans le monde associatif, son statut d'irrigant et, surtout, le fait qu'il ait largement contribué à la mise en place de nouvelles règles font de lui un personnage d'une grande crédibilité sur le sujet pour lequel il a été invité. Ses paroles ont éveillé l'intérêt de l'assistance, la session se déroulant dans un périmètre où les associations d'irrigants ont pris la responsabilité de la gestion de l'eau en façonnant leurs propres règles de gestion (Kadiri et al, 2009). Les témoignages de l'animateur et les débats qui ont suivi ont ensuite constitué, pour un chercheur de l'équipe, une matière riche pour engager la construction avec les agriculteurs d'une grille de lecture sur la durabilité des institutions de gestion de l'eau d'irrigation.…”
Section: Encadré 2 Ostrom Vu Par Les « Façonneurs » De Règlesunclassified
“…The ORMVAs then created almost all the WUAs that still exist in large-scale irrigation schemes today. However, in 2010, most of these WUAs were either inactive or were pursuing only a very limited number of activities , whereas in more traditional small-scale irrigation schemes, and in the smaller-scale Middle Sebou River scheme, these WUAs were more active (Kadiri et al 2009). …”
Section: Intertwined Narratives and Public Policies In Large-scale Irmentioning
confidence: 95%
“…Second, these studies revealed the significant learning process that was taking place in local farmers' organizations, where farmers learned internal check and balance procedures and how to interact with external organizations as partners in the decision-making process (Kadiri et al 2009). In contrast, the studies showed that farmer-initiated collective action was more difficult to achieve at the regional level.…”
Section: Identifying and Analyzing Farmer-led Initiatives And Collectmentioning
confidence: 98%